Conflict Analysis in Fundraising for Mosque Construction from Ralf Dahrendorf’s Perspective - Azmi, Mohammad; Taufiq, Amal (Prodi Sosiologi, Fakultas Ilmu Sosial dan Ilmu Politik, UIN Sunan Ampel Surabaya, 2024)
The problems studied in this research are: how is the process of collecting funds for building a mosque in Serah Village Panceng District Gresik Regency and how conflicts occur in collecting funds involving the construction committee, the mosque administrator and the community as parties who must carry out the decision to give infaq. This research uses qualitative methods with data collection techniques in the form of observation, interviews with related parties, namely the mosque construction committee, mosque ta'mir and residents of the surrounding community. The theory used for analysis uses the perspective of Ralf Dahrendorf's conflict theory. The results of the research show that firstly, because of the high construction costs required for the construction of the mosque, funds were collected by the mosque ta'mir management through various methods, including withdrawing infaq to the community, but the problem is that the committee has determined the nominal amount of the infaq so that it burdens the community. who are classified as economically weak communities. Secondly, the conflict over collecting infaq was also carried out on residents of Serah village who worked as migrant workers in Malaysia, even though their families were already burdened with paying infaq as well.